Enhancing Data Security in IOT-based UAV Networks through Blockchain Integration - Kumar, Vinod; Asthana, Amit; Tripathi, Gaurav (Engineering, Technology & Applied Science Research, 2025)
There is great potential for utilizing Unmanned Aerial Vehicle (UAV) networks for commercial, military, and civil purposes. Therefore, as network volumes increase, communicating within UAV networks poses serious cybersecurity issues. Integrating Blockchain with UAV communication networks can offer a scalable and secure communication method. The proposed approach to a protected and accessible interaction method for peer-to-peer UAV networks integrates blockchain technology, allowing safe, decentralized, and cooperative communication between several entities. This study presents a new consensus-building technique to protect UAV network communications, integrating public key cryptography with blockchain Elliptic Curve Diffie-Hellman (ECDH) using the Secure Hash Algorithm (SHA) to preserve data integrity and secure key exchange to provide confidentiality.